Comparative In Vitro study on the susceptibility and emergence of mutants resistant to danofloxacin and ciprofloxacin among Staphylococcus Aureus isolated from bovine mastitis - Cruz, Andrea D. [UNESP]; De Magalhães Lopes, Carlos A. [UNESP]; Modolo, José R. [UNESP]; Gottschalk, Arnold F. [UNESP] (My University, 1997)
The antimicrobial susceptibility of danofloxacin was compared in vitro with ciprofloxacin against mastitogenic Staphylococcus aureus Danofloxacin was more active than ciprofloxacin, showing minimal inhibitory concentrations (MIC90), minimal bactericidal concentrations (MBC90) and MBC/MIC ratio lower than those of ciprofloxacin. Ciprofloxacin-resistant mutants occurred at higher frequencies (≥10-6) than for danofloxacin (10-9).
Keywords: Ciprofloxacin; Danofloxacin; Resistant mutants; Staphylococcus aureus; Susceptibility